The effect of physical activity on sleep quality among UiTM Seremban 3 students / Nur Najihah ... [et al.]. - Najihah, Nur; Naja, Nurun; Sahira, Naimi; Taufiq, Muhammad; Saad, Akif; Syed Mud Puad, Sharifah Maimunah (2024)
Good physical activity enhances sleep quality. The main purpose of this study is to investigate the effect of physical activity on sleep quality among UiTM Seremban 3 students. It aims to identify key factors contributing to better sleep quality, such as being physically active and having an active lifestyle. Using a Cross-sectional design of a waist-worn accelerometer (Actigraph GT3X+), the study investigates the effect of physical activity on sleep quality among UiTM Seremban 3 students (n=26, age 22.3 ± 1.04) through descriptive analysis and simple linear regression. The study revealed that 38% of 26 participants showed poor physical activity results, with only 8% having a good physical activity level. In addition, 58% experienced average sleep quality, while only 12% experienced good sleep quality. Physical activity has an insignificant effect on sleep quality (Simple Linear Regression = 0.671, p < 0.05). It showed that physical activity has no impact on sleep quality. In conclusion, the majority of students experience a lack of physical activity due to their hectic lifestyles, which results in low physical activity. It is suggested that good physical activity will help you have great sleep quality.